SATELE COMUNEI FĂRĂU DIN JUDEȚUL ALBA (PANGEEA, 2025)
ABSTRACT. The villages of Fărău common, in Alba county. Farau village is located on the the northwestern county of Alba, in the border with Mureş County. It is crossed by Făraă Valley, whose river basin formed Fărău Depression. The commune, besides the village of residence, Farau, include villages: Heria, Sânbenedic, Medveş and Şilea. All villages have a long history, being mentioned in the early Middle Ages. The paper describes the natural, human and historic features of these villages.